195k views
4 votes
Evaluate the function g(x) = -2x2 + 3x - 5 for the input values -2, 0, and 3.

9(-2) = -2(-2)2 + 3(-2) – 5
9(-2) = -2(4) - 6 - 5
g(-2) =-19
g(0) =-5
g(3) =-14

User Overboming
by
5.0k points

1 Answer

4 votes

Answer:

g(-2) = -19, g(0) = -5 and g(3) = -14

Explanation:

The given function is :


g(x) = -2x^2 + 3x - 5 ...(1)

We need to find the function when x = -2,0 and 3.

Put x = -2 in equation (1).


g(-2) = -2(-2)^2 + 3(-2) - 5\\\\=-19

Put x = 0 in equation (1).


g(0) = -2(0)^2 + 3(0) - 5\\\\=-5

Put x = 3 in equation (1).


g(3) = -2(3)^2 + 3(3) - 5\\\\=-14

Hence, g(-2) = -19, g(0) = -5 and g(3) = -14

User Friartuck
by
4.5k points